The role of intellectual capital reporting in the process of supply chain integration of the Military Technical Institute - Savić Aleksandar; Ranisavljević Mihajlo; Mihajlović Milan (Scientific Technical Review)
The Military Technical Institute (MTI) is the largest military scientific and research institution in the Republic of Serbia. It mainly realizes its supply chain from the approved budget funds of the Republic of Serbia, while a smaller part is realized from its own revenues. Her continuous work to improve non-financial performance within the supply chain as well as motivate employees to manage their supply chain integration (SCI) initiatives requires intellectual capital (IC) tracking and reporting. Analysis and reporting on IC in MTI can be done within the human, organizational and social dimensions of IC. This paper will examine the role of IC reporting and examine its impact on SCI in MTI. The aim of the paper is to determine that the monitoring and reporting of IC affects the process of SCI in MTI.